Gestão financeira pessoal utilizando android - El Alam, Najib Rhafael Alves (2011)
The object of this work is the development of a Personal Financial Management application for Android devices, based on an existing web application, communicating with this application via a Web Service, allowing the user to manage their personal finances from Android devices.